Representation of Communicative Competence in English Language Textbooks in Indonesia - Ezis Japar Sidik (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
English textbooks play a paramount role in teaching process, and are expected to contain appropriate contents that can support students to acquire required competences for effective communication. The expected contents should contain different aspects of language abilities or competences well-known as communicative competence. Thus, the present study is aimed to explicate the representation of communicative competence aspects in the spoken dialogue instances contained in Indonesian EFL textbooks.Â Three English textbooks, prepared and designed under the auspices of the Indonesian Ministry of Education and Culture, are selected for the analysis. The findings suggest the textbooks have not provided sufficient dialogues that give useful models for students to use in communication. Amid the scarcity of the models, the available dialogues also do not much reflect how authentic spoken dialogues occur in real-life communication due to inadequacy to reflect real-life communication as insufficient representation of the communicative competence particularly in contained dialogue models.